Zebra mussels (Dreissena polymorpha) as a biomonitor of trace elements along the southern shoreline of Lake Michigan. (6th January 2015) - Shoults‐Wilson, W. Aaron; Elsayed, Norhan; Leckrone, Kristen; Unrine, Jason
Abstract The invasive zebra mussel (Dreissena polymorpha) has become an accepted biomonitor organism for trace elements, but it has yet to be studied along the Lake Michigan shoreline. Likewise, the relationships between tissue concentrations of elements, organism size, and sediment concentrations of elements have not been fully explained. The present study found that a variety of allometric variables such as length, dry tissue mass, shell mass, organism condition indices, and shell thickness index were useful in explaining intrasite variability in elemental concentrations. The flesh condition index (grams of tissue dry mass per gram of shell mass) explained variability at the most sites for most elements. Once allometric intrasite variability was taken into account, additional significant differences were found between sites, although the net effect was small. Significant positive relationships between sediment and tissue concentrations were found for Pb and Zn, with a significant negative relationship for Cd. It was also found that Cu and Zn concentrations in tissues increased significantly along the shoreline in the southeasterly direction, whereas Hg increased in a northwesterly direction. Opportunistic sampling found that zebra mussels accumulate significantly higher concentrations of nearly all elements analyzed compared to Asian clams (Corbicula fluminea) at the same site. The present study demonstrates the need to fully explain natural sources of variability before using biomonitors to explain spatial distributions of trace elements. Environ Toxicol Chem 2014;9999:1–8. © 2014 SETAC